Remarks on the genesis of UNRRA. Negotiations between the Great Powers and selected treaty provisions - Kowalski, Kamil (Annales. Etyka w Życiu Gospodarczym, 2019)
As a conceptual framework, UNRRA referred to one of the four freedoms (freedom from want) mentioned by Franklin D. Roosevelt in a speech given in Congress on January 6, 1946. In the first section, the article presents early attempts to coordinate assistance for the civilian population during World War II (The Committee of Supplies and The Inter-Allied Committee on European Post-War Requirements). The scale of actions taken was very small and insufficient. In January 1942, the USSR proposed the creation of an international organization that would collect information on raw materials and food. This initiative prompted Washington and London to launch a separate competitive project. The organization’s task was to bring help until the state gained economic independence. Therefore, the organization’s goal was not to rebuild the areas affected by war damage in the long term (rehabilitation not reconstruction). In the main part, the article presents the basic issues in dispute when creating the principle of allocating aid, for example, the requirement of consent of the receiving state to receive gifts or the composition of organs of the organization. For this purpose, the exchange of notes between Washington and London was analyzed. Differences of opinions delayed the signing of the contract which did not take place until November 1943.